Sistem Upah Buruh Penambang Pasir Tradisional Persfektip Hukum Islam - Romi Putra Saroji; Supriyadi (TAFAQQUH, 2022)
This study aims to analyze the Islamic Legal Review of the wage system for traditional sand miners in Dusun Ketapang, Desa Gegerung, Kecamatan Lingsar, Kabupaten Lombok Barat, as implemented by the mine owners for both permanent and casual workers. This qualitative research produces descriptive data in the form of written or spoken words from interviews and observations, using a normative sociological approach that connects the norms of wage practices with the ijarah concept in theory and practice. The analysis uses the theory of ijarah and principles of Islamic contracts. The findings show that the wage system in this area does not align with Islamic law, as there is no prior agreement or understanding between the mine owner and the miners regarding the wage rate, leading to uncertainty and a disparity between the two parties. In an Islamic wage system, it is crucial that neither party feels disadvantaged.